ANALISIS HUBUNGAN KEKERABATAN BAHASA JAWA DENGAN BAHASA BALI: KAJIAN LINGUISTIK HISTORIS KOMPARATIF : Linguistik Historis Komparatif - Ramadhani, Nova Putri (Jurnal Pena Indonesia, 2024)
The aim of this study was to find out the language kinship relationship between Javanese and Balinese. The methods used are descriptive qualitative methods and quantitative methods with data collection to conduct library studies on scientific articles related to the kinship relationship between Javanese and Balinese languages. The object of this study was 60 pairs of Javanese and Balinese vocabulary that have a kinship relationship. The conclusion of this study is that there is a kinship relationship between Javanese and Balinese, with a kinship rate of 30%. This kinship was discovered through analysis of 60 pairs of vocabulary from both languages. Of the 60 pairs, there were 19 pairs indicating kinship based on phonemic correspondence, 27 pairs of identical vocabulary, and 14 pairs of vocabulary that had one different phoneme. The entirety of this research, which uses a comparative historical linguistic approach, provides an in-depth understanding of the history and evolution of the Javanese and Balinese languages. The comparison of these linguistic aspects is the basis for understanding the uniqueness of each language while revealing the richness of linguistic heritage in the archipelago region. Keywords: Comparative Historical Linguistics, Javanese, Balinese, Language Kinship